Diagnostic accuracy of history, laryngoscopy, and stroboscopy12. (15th October 2012) - Paul, Benjamin C.; Chen, Si; Sridharan, Shaum; Fang, Yixin; Amin, Milan R.; Branski, Ryan C.
Abstract Objectives/Hypothesis: Although clinical dogma suggests the value of laryngeal visualization (flexible laryngoscopy and stroboscopy) in dysphonic patients, recently published clinical guidelines suggest that, in many cases, history and/or physical examination are sufficient to guide clinical decision‐making regarding the timing of such examinations. We sought to prospectively quantify the diagnostic accuracy of history, laryngoscopy, and stroboscopy using direct laryngoscopy as the gold standard. Study Design: Expert survey. Methods: Six laryngologists were presented with vignettes including history and physical examination (HPE), laryngosocpy, and stroboscopy. Questions regarding diagnosis, the certainty of diagnosis, and subsequent management plans were posed. Operative findings via direct laryngoscopy were employed as a comparator. Results: The diagnostic accuracy of HPE was quite low (5%). The accuracy of diagnosis increased substantially following laryngeal imaging; 68.3% for both flexible laryngoscopy and stroboscopy. Particular diagnoses were more consistently identified; cancer, for example, was much more accurately identified on laryngoscopy (100%) and stroboscopy (100%) rather than HPE alone (33%). Cancer was selected as the diagnosis in 10 of 60 HPEs, though was only correct once and missed in five cases. In contrast, no diagnoses of cancer were missed following laryngoscopic and/or stroboscopic examinations. Conclusion: These findings confirm the value of laryngeal visualization (flexible laryngoscopy and stroboscopy) in dysphonic patients, and the lack of accuracy of history and physical examination in determining the diagnosis in patients with hoarseness. Laryngoscope, 2013